Urban parks and natural heritage in West Africa: from the colonial period to the 50th anniversary of independence - (:unkn) unknown (My University, 2011)
In West African countries, the usual distinction between urban spaces and bush often meets the UNESCO distinction between cultural heritage and natural heritage. Historical and ethnographical study of the place of nature in West African capitals, in particular the one of urban parks, forces to question this distinction. In Ouagadougou and in Bamako, we can observe a renewal of urban parks and reclaiming of forests that were listed under the colonial era. These projects for planning urban parks are conceived as heritage projects, safeguarding of the biodiversity, but also building places of memory. The Parc Urbain Bangr Weoogo (PUBW) in Ouagadougou incorporates a small museum of natural history and a menagerie, whereas the national park of Mali in Bamako, opened for the 50th anniversary of Independence, incorporates the famous National Museum of Mali. While these projects are politically driven, they have to compose in the same time with ritual practices of the concerned territories. Both studied parks are therefore hybrid and bring us to rethink the distinction between natural heritage and cultural heritage and to articulate politics of nature and urban memories in West Africa.
Keywords: African Research